Quality paper an ISO 9001 based approach for the implementation of process FMEA in the Brazilian automotive industry - de Aguiar, Dimas Campos; Salomon, Valério Antonio Pamplona [UNESP]; Mello, Carlos Henrique Pereira (Emerald, 2015)
Purpose – The purpose of this paper is to present a structured way for the definitions of the Process Failure Mode and Effect Analysis (FMEA) attributes, such as potential failure mode, potential cause and potential effect, in order to make it simpler to define the controls and scores. Design/methodology/approach – This study performs, through a case study in incoming inspection of raw material, the comparison of a conventional application of the Process FMEA with a proposal based on the concepts of process approach defined by ISO 9001. Findings – Even written in a form similar to a script, the application of Process FMEA is a very complex activity and, like most quality tools, before being applied, FMEA should be clearly understood by the team. One way to facilitate this understanding is considering the sequence of events in the failures analysis to understand their causes and effects, just as are the sequences of inputs and outputs in the definition of the process approach addressed in ISO 9001. Originality/value – This paper shows a simple way to better structure Process FMEA, facilitating meetings with multidisciplinary teams.
Keywords: ISO 9001; Process approach; Process FMEA